Climate change, rice crops and violence evidence from Indonesia - Caruso, Raul 1972-; Petrarca, Ilaria; Ricciuti, Roberto 1972- (CESifo, 2014)
This paper adopts an instrumental variable approach to uncover the impact of variations in minimum temperature on emergence and severity of actual violence through the effect on food availability, captured by rice crops per capita. The link between increase in minimum temperature and rice crops is suggested by natural science literature. We use Indonesia as a case study over the period 1990-2003. Results show that an increase of the minimum temperature during the core month of the "wet planting season", i.e. December, determines an increase in violence fuelled by the reduction in future rice production per capita.
Literaturverz. S.19-23